Peranan Akidah dalam Perancangan Pembangunan Ummah: Satu Analisis dalam Konteks Masyarakat Kini - Hamat, Mohd Fauzi (Jurnal Usuluddin, 2002)
The significance of human development especially human resource development (HRM) and its relations with the role of Islamic theology is commonly understood by many Muslim scholars based on their understanding of the Impact of Islamic theology in changing human mind set, act and behavior. This article will discuss that role in relation to the human development in Malaysia. Some suggestions are also being raised to ensure that the study of Islamic theology in our country would give the maximum impact in changing our life and developing our society.